Chemical Profiling of Sea Fennel (Crithmum maritimum L., Apiaceae) Essential Oils and Their Isolation Residual Waste-Waters - Olivera Politeo; Marijana Popović; Maja Veršić Bratinčević; Kristina Kovačević; Branimir Urlić; Ivana Generalić Mekinić (Plants, 2023)
Sea fennel (Crithmum maritimum L.) is a wild-growing halophyte used in cuisine, traditional medicine or cosmetic products for its beneficial nutritive value and pleasant sensory characteristics. This study aimed to investigate sea fennel essential oils (EOs) from different parts of the plant (flowers, leaves and stems) and the corresponding hydrodistillation by-products (residual water) to validate their potential use and application in different industries. EOs were analyzed by gas chromatography coupled with mass spectrometry (GC-MS), while the phenolic profile of the residual water was analyzed by high-performance liquid chromatography (HPLC) and spectrophotometric methods. The EO analysis confirmed the presence of 14 compounds, dominated by sabinene (from 42.55 to 51.47%) and limonene (from 36.28 to 43.58%), while among the 12 detected phenolics, chlorogenic acid and its isomers (cryptochlorogenic and neochlorogenic acid) were found in the highest concentrations. Total phenolic, flavonoid and tannin contents were concentrated in the order flowers > leaves > stems. Although the sea fennel samples showed differences in chemical profiles, overall they were rich in bioactive compounds with relatively high amounts of key compounds with already proved good biological properties, especially in waste-water, indicating great potential for re-use in accordance with green processing technology trends.